Patterns of Global and Regional Integration in the East African Community - Sebastian Krantz (Kiel Institute for the World Economy (IfW Kiel), 2024)
Using detailed global trade and novel Multi-Region Input-Output (MRIO) data, this paper examines the East African Community's (EAC) global and regional integration through trade, global, and regional value chains (GVCs and RVCs). With surgical attention to detail, the first part of the paper dissects key patterns and trends of EAC members' participation in global and regional trade and production networks at the aggregate, bilateral, sectoral, and bilateral-sectoral levels. The second part then provides causal reduced-form evidence for the economic benefits of EAC integration through trade, GVCs, and RVCs at the sector level. Findings imply that the region is moderately integrated into GVCs and RCVs but shows no overall trend towards greater integration. Regional integration is advancing in agriculture and food processing, and Kenya is becoming a more dominant regional supplier of manufactures. Integration through trade and GVCs positively affects economic development in the region, particularly deeper forward GVC linkages in manufacturing. Deepening regional trade and forward linkages yields additional economic benefits vis-a-vis global linkages.
Keywords: F14; F15; O11; 330; GVCs; RVCs; EAC; trade; regional integration; economic development